Australia as a rising middle power - Davis, Malcolm (Nanyang Technological University, 2020)
This paper examines the key drivers shaping Australia’s role as a middle power in an era of intensifying US-China strategic competition. These drivers include the influence of strategic geography; its historical legacy in international affairs; the impact of its economic relationships with states in the Indo-Pacific region; the changing demands of defence policy, including the potential offered by rapid technological change; and, the impact of climate change, resource constraints and demographic factors. The paper considers three possible scenarios that will shape Australia’s middle power policy choices – a US-China strategic equilibrium; a “China crash” scenario that promotes a more nationalist and assertive Chinese foreign policy; and a third “major power conflict” scenario where competition extends into military conflict. The paper concludes that Australia cannot maintain a delicate balance between its strategic alliance with the US and trading relationship with China. It argues there is a need for Australia to adopt a deeper strategic alliance with the US while promoting closer ties with its partners in the Indo-Pacific and supporting the growth of a Free and Open Indo-Pacific region to counterbalance growing Chinese power. Australia needs to embrace an Indo-Pacific step up, and as a middle power, reduce the prospect of a Sino-centric regional order emerging.